Domínio cognitivo requerido do farmacêutico generalista nas provas do ENADE sob a perspectiva da Taxonomia de Bloom revisada - Ott, Joice Nedel (2021)
Assessment is one of the essential dimensions of the learning process. In higher education, the National Student Performance Exam (ENADE) aims to accompany the academic learning process in relation to the Curriculum Guidelines, the syllabus and the development of competencies and skills necessary for general and professional training. As a possibility of classification and hierarchical organization of educational objectives, Bloom's Taxonomy allows to determine the type of knowledge acquired by the student (effective, conceptual, procedural and metacognitive) and the cognitive processes used in solving the questions (remember, understand, apply, analyze , evaluate and create). The objective of the study was to analyze the cognitive domain of the Revised Bloom Taxonomy (TBR) required in the ENADE tests of undergraduate Pharmacy graduates according to the National Curriculum Guidelines for Pharmacy (DCNF). Through two research questionnaires, questions from ENADE representative of the universe of three editions of the Pharmacy course (2010, 2013 and 2016) were analyzed in the opinion of the coordinators and teachers and using a template proposed by evaluators as a reference to the dimensions of the TBR. Most of the questions included in the study corresponded to the conceptual level of the Knowledge Dimension and the cognitive category to understand. There was an inverse and moderate correlation (r=-0.33; p=0.088) between the Facility Index and the TBR Cognitive Processes Dimension, based on the analysis of the teachers / coordinators, confirmed by the consensual feedback (r=-0.38; p=0.047), statistically significant. Through the reference classification, a direct and moderate correlation was obtained between the Discrimination Index and the TBR Knowledge Dimension (r=0.29; p=0.129). The ENADE concepts of Pharmacy courses in operation in RS, over nine years, remained stable; whereas the correlation between the Facility Index and the Discrimination Index of the questions was direct and strong (r=0.69; p<0.001*) in 2010 and 2016 (r=0.58; p=0.576) and moderate in 2013 (r=0.32; p=0.079) and 2019 (r=0.31; p=0.312). It emphasizes the need for a critical analysis in elaborating the items of the ENADE test, with prospecting in the TBR in order to contemplate higher cognitive levels. And, above all, reinforce the teaching role, facilitator and mediator of the teaching-learning process, contributors to the evaluation process as an elaborator of questions and a direct agent for changing the student's condition.